Menakar Peran Digital Leadership dalam Meningkatkan Kinerja Perusahaan di Era Pandemi Covid-19 - Gede Sri Darma; Luh Asri Martani (Ideas Publishing, 2023)
Education in Indonesia is currently experiencing rapid progress in technology, especially in the era of the Covid-19 pandemic which forces students to study online, so there needs to be innovation from company leaders engaged in education to seek digital-based education. This study aims to analyze the leadership s efforts to understand the people around the company regarding the use of technology, building a digital organization, and integrating technology trends in the era of the Covid-19 pandemic. The research method in this study used a qualitative descriptive method. Data collection techniques are observation and interviews. The subjects of this research are the owner, head of the field, and staff of Triton Denpasar. The data analysis technique used is data reduction, data presentation, and conclusion drawing. The results of the study found that leadership efforts in building digital organizations within the company in the Covid-19 pandemic era started from providing training to staff and integrating technology in daily office work and using technology in the registration process, learning process, socialization to the learning evaluation process.